Energy component of the Program of cooperation between the regions of the Far East and Eastern Siberia of the Russian Federation and the northeast area of China People's Republic (2009-2018) - B. G. Saneev; M. N. Lopatina (Контуры глобальных трансформаций: политика, экономика, право, 2014)
The authors examine the main directions of the energy cooperation between Russia and China that were developed in the Program approved by the parties in 2009. Analysis of a number of the key projects of the regional cooperation between Russia and China shows that the innovative projects related to alternative and renewable energy sources will be implemented mainly by China, and the projects related to fuel extraction (coal. oil) and electricity production (even with the use of modern technology) by conventional methods will be implemented by Russia. Program according to the authors’ opinion should be supplemented by other projects that would reflect the mutual interest of Russia and China.